'Fantastic Modernism': Walter Pater, Botticelli, and Simonetta. Issue 2 (2nd April 2016) - Cheeke, Stephen
Abstract: 'Fantastic modernism' is the phrase Margaret Oliphant used to describe what she took to be the 'grotesque misrepresentation' of Walter Pater's chapter on Botticelli in The Renaissance (1873). She meant that Pater's reading of the painter's supposed 'heresy', and the attribution of the melancholy of his Madonnas to an anti-Christian sentiment, was an historical anachronism of the worst kind. This article looks at Pater's Botticelli in relation to the history of the 'myth' of Simonetta Vespucci, traces the importance of this myth to Pater's reading, and presents a more sympathetic case for the value of creative anachronism as a way of encountering the past. The notion of a single historical person ('tradition connects it with Simonetta') who took the roles of mythological and Christian personae alike underpins the central argument of Pater's chapter. According to Pater, Botticelli's paintings present a sequence of female persons in which is repeated the same psychological dilemma—a resistance to the role she is required to play within a mythological or religious narrative. The article connects this notion of a psychologized dilemma to the broader question of the encounter between classical antiquity and Christianity in the Florentine Renaissance, as it was conceived in nineteenth-century writing on art, comparing Pater's reading with those of John Ruskin, John Addington Symonds and others. Finally, some observations are made about the afterlife of Botticelli's principal female figure and its relation to Pater's reading.